2016
DOI: 10.1016/j.psyneuen.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment is associated with lower cortisol awakening and blunted dehydroepiandrosterone responses

Abstract: DisclaimerThe University of Gloucestershire has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material.The University of Gloucestershire makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.The University of Gloucestershire makes no representation that the use of the materials will not infringe any patent, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…In this context, a better understanding of the neurobiology of stress, as well as stress resilience ( McEwen et al., 2015b , Russo et al., 2012 ), in human subjects is becoming increasingly relevant for individual and population health. Although some features of this field focus on chronic naturalistic stressors, such as unemployment ( Dettenborn et al., 2010 , Gallagher et al., 2016 ) or caring for a relative with dementia ( Clipp and George, 1993 , Kim and Schulz, 2008 ), valuable insights have also been derived from laboratory studies based on acute stress paradigms (c.f. Bali and Jaggi, 2015 ; for a review).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a better understanding of the neurobiology of stress, as well as stress resilience ( McEwen et al., 2015b , Russo et al., 2012 ), in human subjects is becoming increasingly relevant for individual and population health. Although some features of this field focus on chronic naturalistic stressors, such as unemployment ( Dettenborn et al., 2010 , Gallagher et al., 2016 ) or caring for a relative with dementia ( Clipp and George, 1993 , Kim and Schulz, 2008 ), valuable insights have also been derived from laboratory studies based on acute stress paradigms (c.f. Bali and Jaggi, 2015 ; for a review).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, being employed is a source of financial security, provides people the opportunity to fulfil a social and family role, and is important for physical and mental health [ 3 , 4 ]. Unemployment means a change in social position, particularly in the family, and is usually perceived as a very stressful life event [ 5 , 6 , 7 ] with relevant consequences for health [ 8 , 9 ]. Precise and commonly shared definitions of employment and unemployment status are lacking and different studies addressed them differently: these include long-term vs. short-term unemployment, or temporary interruptions, and are referred to people of working age (but not student or in training) that are actively looking for work.…”
Section: Introductionmentioning
confidence: 99%
“…However, only social support from significant others, and not from family and friends, was found to be associated with the CAR, which may help explain the null findings of the current study given that we examined total social support without taking into account the source of support. However, there have also been other studies among pregnant and non‐pregnant women alike that have found no association between social support and the CAR (Gallagher, Sumner, Muldoon, Creaven, & Hannigan, ; Simon et al, ). These results suggest that if associations exist between greater levels of perceived social support and lower perceived stress reactivity, these psychological effects may not always extend to biological changes in stress reactivity.…”
Section: Discussionmentioning
confidence: 95%